Effect of phosphate on the expression of protein-Ser/Thr kinase pkg2 in Streptomyces granaticolor - Nováková, L; Nádvorník, R; Vomastek, T; Janecek, J; Branny, P (Folia microbiologica, 2005)
A time-correlated expression of eukaryotic-like protein Ser/Thr kinase Pkg2 of Streptomyces granaticolor was investigated by reverse transcriptase-polymerase chain reaction (RT-PCR) and by transcriptional fusion experiments. In a complex medium the activity of pkg2 promoter was constant during the life cycle. Direct RNA analysis proved the presence of corresponding pkg2 transcript. S1 nuclease protection analysis of the transcription initiation site showed that pkg2 gene is expressed as a leaderless mRNA. Under phosphate starvation the promoter activity was detectable merely in the early exponential phase. Under these conditions turning off of pkg2 promoter and cessation of pkg2 transcript level coincided with the start of granaticin production.
Keywords: Protein Serine-Threonine Kinases; Transcription, Genetic; Catechol 2,3-Dioxygenase; genetická transkripce; Culture Media; protein-serin-threoninkinasy; promotorové oblasti (genetika); Gene Expression Regulation, Bacterial; Phosphates; regulace genové exprese u bakterií; kultivační média; fosfáty; Streptomyces; katechol-2,3-dioxygenasa; Promoter Regions, Genetic